Improving Students' Descriptive Writing Skills Through Collaborative Writing Using Canva Application - Dyah Ayu Riesnawati, Happy; Susanti, Arik (Pascasarjana Universitas Negeri Makassar, 2024)
Developing descriptive writing skills equips students with the ability to communicate effectively, enhances their observation and critical thinking abilities, encourages creative expression, and fosters empathy and perspective-taking. These skills are valuable not only in academic settings but also in various personal and professional contexts, allowing students to effectively engage their audience and express themselves with clarity and impact. Thus, students need collaborative learning and appropriate instructional media to develop their descriptive writing perfectly. This study aims to determine whether the collaborative writing method using the Canva application can improve EFL students' abilities in descriptive writing. This study used one group pretest and posttest design involving 32 students at one of the junior high schools in Gresik. The data was collected through pretest and posttest in the form of essays. The results of the paired sample t-test showed a significant value of .000 less than .05, which can be interpreted that there is a significant difference in the students' pretest and posttest. The conclusion obtained that the collaborative writing method using the Canva application can improve students' descriptive writing skills. Teachers can utilize this type of research to effectively instruct pertinent subjects to their students. Additionally, it serves as a source of inspiration for other scholars, encouraging them to delve into more profound investigations.